Temporal and spatial precursors in ionospheric total electron content of the 16 October 1999 Mw7.1 Hector Mine earthquake. Issue 10 (3rd October 2013) - Su, Y. C.; Liu, J. Y.; Chen, S. P.; Tsai, H. F.; Chen, M. Q.
Abstract [1] In this paper, temporal and spatial analyses are employed to detect seismo‐ionospheric precursors (SIPs) in the ionospheric total electron content (TEC) during the 16 October 1999 Mw7.1 Hector Mine earthquake. To discriminate anomalies caused by global effects, such as solar radiations, magnetic storms, etc., and local effects, such as earthquake, we cross‐examine the GPS TECs and their gradients in the eastward and northward directions at epicenter/centers of the Hector Mine area and the other two reference areas at similar magnetic latitudes in Europe and Japan. Temporal variations of the northward TEC gradient suggest SIPs most likely appearing on days 6–5 before the earthquake. A global search by using the TEC of the global ionosphere map shows that the TEC increase and decrease anomalies continuously and specifically appear around the epicenter on day 5 before the earthquake.